Analisis Dampak Program Rehabilitasi Rumah Tidak Layak Huni Terhadap Lingkungan, Ekonomi dan Sosial Masyarakat di Kabupaten Bireuen - Ismasudayanti; Cut Azizah; Sitti Zubaidah (Jurnal Serambi Engineering, 2024)
The Uninhabitable Houses Programme is a government programme to increase the number of habitable houses for low-income people who do not yet have a house that meets the appropriate standards. This government programme is better known as the Self-Help Housing Stimulant Assistance Programme or BSPS. This government assistance has had environmental, economic and social impacts on the people of Bireuen District. The aim of this research is to determine the condition of uninhabitable houses in Bireuen Regency after renovation and to analyse the impact of the Uninhabitable House Rehabilitation Program on the environmental, social and economic conditions of the community in Bireuen Regency. The method used in this research is descriptive with a qualitative approach. The data collection techniques used were direct observation, questionnaires and primary data. The results of the research showed that the programme of rehabilitation of uninhabitable houses in Bireuen Regency had an impact on the community environment, namely the improvement of the quality of the houses in terms of the availability of access to sanitation and clean water, and the fulfilment of lighting and ventilation standards.